The book of Ruth - Hubbard, Robert L. 1943-; Bible. O.T. Ruth English Hubbard 1988 (Grand Rapids, MI Eerdmans, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Ruth -- commentaries